Studio Borgerstein 2021 : Outsider Art. - Muylle, Pierre (Sint-Katelijne-Waver : Studio Borgerstein, 2021)
Oste, François ; Verstrepen, Georg ; Cortebeeck, Hans ; Vander Vliet, Ivan ; Van Geesberghen, John ; Wuyts, Jan ; De Decker, Kathy ; Cloostermans, Jef ; Van Muylder, Luc ; Lannoo, Nathalie ; Laroche, Monica ; Thielens, Martine ; Nuyttens, Palmer ; Michiels, Stijn ; Hingst, Wytze ; Serneels, Sylvain ; Langhmans, Sven ; Backs, Yvonne ; Perez, Sonny ; Goovaerts, Rozette ; Van Rompaey, Inge ; Buyck, Carlo ; Cretoir, Clement ; Dillen, Jean
Het nieuwe geniaal, Cultuurcentrum Mechelen, Mechelen, 2021
boek